2003
DOI: 10.1159/000071856
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Adenocarcinoma of the Bladder in a Male Patient: Clinicopathologic Analysis of a Case

Abstract: Clear cell adenocarcinoma arising in the lower urinary tract is unusual. We report a case of clear cell adenocarcinoma of the bladder in a 54-year-old male. Cystoscopic examination revealed a tumour arising from the dome of the urinary bladder. Histologically, the tumour was chiefly composed of tubulocystic and papillary glands lined by glycogen-rich, cubical or hobnail cells with clear to eosinophilic cytoplasm. The tumour infiltrated into the inner muscular layer. The patient was treated by partial cystectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Signori et al [ 22 ] reported a case of clear cell adenocarcinoma of the urinary bladder in 54-year-old man. He underwent cystoscopy which revealed a tumour arising from the dome of his urinary bladder.…”
Section: Discussion and Miscellaneous Narrations From Reported Casmentioning
confidence: 99%
“…Signori et al [ 22 ] reported a case of clear cell adenocarcinoma of the urinary bladder in 54-year-old man. He underwent cystoscopy which revealed a tumour arising from the dome of his urinary bladder.…”
Section: Discussion and Miscellaneous Narrations From Reported Casmentioning
confidence: 99%
“…While it has been previously observed that CCA may focally resemble NA, this study is the first to document a series of CCA which closely resembles NA throughout the tumor. As most regard the presence of solid sheets of cells, abundant clear cytoplasm, and significant nuclear atypia as keys to the diagnosis of CCA, the absence of these features make an accurate diagnosis of this entity more challenging, even in larger tissue samples [4,5,8,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also questioned whether NA is a precursor lesion to CCA [6,21,22]. A history of prior NA in some patients, as well as some similarity in immunohistochemical staining, has been used to favor this hypothesis [1,3,6,8,23]. Moreover, a single case report has provided molecular evidence of a common origin of the NA and CCA, although it is only a single case and the possibility exists that the "NA" in this case could have been a NAlike CCA [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gross appearance is nonspecific, but the tumor frequently grows as a papillary mass [1, 8–10]. The most common locations are the bladder neck, trigone, and lateral bladder wall [1, 4, 6, 9, 11] and the dome [12]. The most common architectural pattern is tubulocystic, followed by papillary, glandular, and diffuse [1, 8–13].…”
Section: Introductionmentioning
confidence: 99%